Sliding Mode Control in Finite Time Stabilization for Synchronization of Chaotic Systems. (30th October 2013) - Zhao, Zhan-Shan; Zhang, Jing; Sun, Lian-Kun
Abstract : An adaptive sliding mode control for chaotic systems synchronization is considered. The design of robust finite time convergent controller is based on geometric homogeneity and integral sliding mode manifold. The knowledge of the upper bound of the system uncertainties is not prior required. The chaos synchronization is presented to system stability based on the Lyapunov stability theory. The simulation results show the effectiveness of the proposed method.